Central African Economic and Monetary Community : A New Medium-Term Approach - de Zamaroczy, Mario (Departmental Papers; Departmental Paper ;, 2018)
This paper discusses possible reserve management approaches in the Central African Economic and Monetary Community (CEMAC). The paper looks beyond the region's current oil crisis and proposes a new approach to international reserve management in the medium term.